(untitled) (The Pretoria Student Law Review, 2021)
This article evaluates the vaccine rollout plan in South Africa and whether it intends to achieve herd immunity or gain more power for the government. The importance of South Africa achieving herd immunity will be considered alongside the restrictions preventing the private sector from gaining access to vaccines thus, arguably, slowing the process of achieving herd immunity. Finally, this article explores different strategies that the government could consider in order to accelerate the vaccination rollout without relinquishing its political power.